З історії дослідження випалювальних споруд Х-ХІІІ століть Лівобережної України - Троцька, В. (Сiверянський лiтопис, 2011)
Про історію дослідження гончарних горнів доби Русі на території Лівобережної України (за архівними джерелами та публікаціями вчених). Об истории исследования гончарных горнов времен Руси на территории Левобережной Украины (по архивным источникам и публикациям ученых). The article deals with the history of the studying of pottery kilns, dated with the epoch of Rus (10 th — 13 th centuries) on the terrytory of Left Banke Dnipro Ukraine (based on the archival sources and the published works of the scientists).